Коммуникативная онтология А. Пушкина в одесской лирике. «Впечатленья бытия» и текст как инобытие автора - Уразаева, Куралай Бибиталыевна (SlavVaria, 2022)
A. Pushkin's Communicative Ontology in Odessa lyrics. “Impressions of Being” and the Text as the Author's Otherness. The article is devoted to the study of Pushkin's ontology with application of communicative ontology. The methods of communicative ontology in the works of Yu. Lotman about the Odessa lyrics of A. Pushkin are investigated, the parameters of the ontological dimension of communication are systematized. The substantiation of Pushkin's “Odessa text” as an otherness is carried out as a correlation of the author's text with the system of contexts forming it. This view contributed to Bonapartism contexts’ classification, Orthodoxy and the Faustian text as philosophical and artistic parameters of Pushkin's ontology. The prospects for the development of Yu. Lotman's ideas and methods for the analysis of Bonapartism and its para-doxical meaning for Russian history, Orthodoxy as a philosophy of religious artistry and the Faustian text are shown.